2009
DOI: 10.1101/gad.1806309
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Wnt pathway inhibits timely myelination and remyelination in the mammalian CNS

Abstract: The progressive loss of CNS myelin in patients with multiple sclerosis (MS) has been proposed to result from the combined effects of damage to oligodendrocytes and failure of remyelination. A common feature of demyelinated lesions is the presence of oligodendrocyte precursors (OLPs) blocked at a premyelinating stage. However, the mechanistic basis for inhibition of myelin repair is incompletely understood. To identify novel regulators of OLP differentiation, potentially dysregulated during repair, we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
638
5
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 565 publications
(679 citation statements)
references
References 47 publications
35
638
5
1
Order By: Relevance
“…Analysis of gene expression profiles during development in the normal adult brain and during demyelination identified several novel regulatory pathways of oligodendrocyte differentiation. These studies showed that oligodendrocyte differentiation and remyelination are dependent on retinoid-X receptor-gamma receptor agonists [115] and on Wnt-beta-catenin signaling [116]. In addition, type 2 cyclin dependent kinase (also known as cdk2), which controls the cell cycle, does not interfere with myelination during development, but its knock-out facilitates remyelination [117].…”
Section: Myelin Regeneration Fails In Msmentioning
confidence: 99%
“…Analysis of gene expression profiles during development in the normal adult brain and during demyelination identified several novel regulatory pathways of oligodendrocyte differentiation. These studies showed that oligodendrocyte differentiation and remyelination are dependent on retinoid-X receptor-gamma receptor agonists [115] and on Wnt-beta-catenin signaling [116]. In addition, type 2 cyclin dependent kinase (also known as cdk2), which controls the cell cycle, does not interfere with myelination during development, but its knock-out facilitates remyelination [117].…”
Section: Myelin Regeneration Fails In Msmentioning
confidence: 99%
“…A screen for transcription factors associated with CNS remyelination in experimentally demyelinated mice led to the identification of Tcf4 expression in oligodendrocyte lineage cells and the elucidation of the canonical Wnt pathway as a negative regulator of precursor differentiation [55]. Tcf4 is expressed in the mouse white matter immediately after birth, but it is barely detectable in the adult [55][56][57].…”
Section: Wnt Signalingmentioning
confidence: 99%
“…Tcf4 is expressed in the mouse white matter immediately after birth, but it is barely detectable in the adult [55][56][57]. However, following CNS injury, Tcf4 is reexpressed and upregulated in OPCs that are recruited to the lesion [56].…”
Section: Wnt Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the ΔExon3 mutation of β-catenin [1][2][3][4] , which stabilizes β-catenin by deletion …”
mentioning
confidence: 99%